Exploring Prevalence and Implications of Burnout Among Nurse Practitioners in Canada - Heale, Roberta (European Scientific Journal, ESJ, 2025)
Introduction: Nurse Practitioners are experiencing unprecedented levels of burnout which is exacerbated by factors unique to this professional group. Additional factors include undervalued professional worth, lack of autonomy, and organizational and systems pressures. This study was conducted to explore NP Burnout in Canada. Methods: The NP Burnout Survey, which was designed to capture the unique factors impacting NP burnout, was delivered to 229 NPs across Canada. Responses underwent descriptive and binomial logistic regression analysis. Results: More than one-third of NPs are experiencing high levels of burnout. NPs with high burnout are 17 times more likely to leave their position and 66 times more likely to leave the profession. Conclusion: Urgent attention and viable solutions are required to mitigate NP’s exodus from the profession. Addressing the issues impacting NP burnout will ensure that this profession will meet its full potential in Canada’s healthcare system.